2018
DOI: 10.1093/jxb/ery441
|View full text |Cite
|
Sign up to set email alerts
|

Control of plastidial metabolism by the Clp protease complex

Abstract: Plant metabolism is strongly dependent on plastids. Besides hosting the photosynthetic machinery, these endosymbiotic organelles synthesize starch, fatty acids, amino acids, nucleotides, tetrapyrroles, and isoprenoids. Virtually all enzymes involved in plastid-localized metabolic pathways are encoded by the nuclear genome and imported into plastids. Once there, protein quality control systems ensure proper folding of the mature forms and remove irreversibly damaged proteins. The Clp protease is the main machin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
59
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 78 publications
(90 reference statements)
0
59
0
1
Order By: Relevance
“…Clp proteases are also present in photosynthetic bacteria such as Synechococcus elongatus , in non‐photosynthetic apicoplasts of the malaria pathogen Plasmodium falciparum , in plant chloroplasts and mitochondria , as well as mitochondria of non‐plant eukaryotes . The chloroplast Clp proteolytic system plays an essential role in chloroplast biogenesis, proteostasis, and metabolism . Many α‐proteobacteria such as Agrobacterium tumefaciens and cyanobacteria such as S. elongatus contain two ClpS homologs, ClpS1 similar to bacterial ClpS, and the more divergent ClpS2 .…”
mentioning
confidence: 99%
“…Clp proteases are also present in photosynthetic bacteria such as Synechococcus elongatus , in non‐photosynthetic apicoplasts of the malaria pathogen Plasmodium falciparum , in plant chloroplasts and mitochondria , as well as mitochondria of non‐plant eukaryotes . The chloroplast Clp proteolytic system plays an essential role in chloroplast biogenesis, proteostasis, and metabolism . Many α‐proteobacteria such as Agrobacterium tumefaciens and cyanobacteria such as S. elongatus contain two ClpS homologs, ClpS1 similar to bacterial ClpS, and the more divergent ClpS2 .…”
mentioning
confidence: 99%
“…Furthermore, proteases are present in all cellular compartments and can exert specific functions in these in isolation from the rest of the cell. Rodriguez-Concepcion et al (2019) review the existing literature on the chloroplast-localized Clp complexes and substrates. While the authors put forward clear rules as to what constitutes a confirmed Clp substrate, definite proof is hard to come by and ideally involves both in vivo and in vitro confirmation.…”
Section: Regulation Of Protease Activitymentioning
confidence: 99%
“…This is catalogued in the MEROPS database (Rawlings et al , 2018) with class names based on the active site amino acid or metal that performs the hydrolysis, resulting in five major groups in plants: serine (S), aspartate (A), cysteine (C), threonine (T) and metallo-proteases (M) (Box 1). Papers in this issue focus on members of the pepsin-like family (A1 using the MEROPS protease nomenclature) of aspartic proteases (Soares et al , 2019a), Clp (Caseinolytic protease) serine proteases (S14) (Rodriguez-Concepcion et al , 2019), Lon proteases (named after the long filament phenotype of bacterial mutant cells; S16) (Tsitsekian et al , 2019) and metacaspases (C14B) (Klemencic and Funk, 2019). Subtilisin-like serine proteases or subtilases (S8) have also recently been reviewed (Schaller et al , 2018).…”
mentioning
confidence: 99%
“…A distinctive feature of chromoplasts compared to other heterotrophic plastid types is the massive synthesis and storage of carotenoids. Recently a DnaJ-like chaperone termed ORANGE (OR) was reported to promote carotenoid biosynthesis by increasing the amount of carotenoid biosynthetic enzymes through functional interactions with the stromal Clp protease complex (Rodriguez-Concepcion et al, 2019). OR promotes the correct folding of phytoene synthase (PSY) and such increases its activity and prevents misfolding and removal by the Clp protease complex, which is similar to the anticipated function of ClpB3 in the stabilization of deoxyxylulose 5-phosphate synthase (DXS) (D'Andrea and Rodriguez-Concepcion, 2019).…”
Section: Introductionmentioning
confidence: 99%